Improving Event Extraction via Multimodal Integration - Zhang, Tongtao; Whitehead, Spencer; Zhang, Hanwang; Li, Hongzhi; Ellis, Joseph; Huang, Lifu; Liu, Wei; Ji, Heng; Chang, Shih-Fu (Proceedings of the 25th ACM international conference on Multimedia, 2017)
In this paper, we focus on improving Event Extraction (EE) by incorporating visual knowledge with words and phrases from text documents. We rst discover visual paerns from large-scale textimage pairs in a weakly-supervised manner and then propose a multimodal event extraction algorithm where the event extractor is jointly trained with textual features and visual paerns. Extensive experimental results on benchmark data sets demonstrate that the proposed multimodal EE method can achieve signicantly beer performance on event extraction: absolute 7.1% F-score gain on event trigger labeling and 8.5% F-score gain on event argument labeling.